2019
DOI: 10.1128/aem.00550-19
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Responses of Shewanella decolorationis to Toxic Organic Extracellular Electron Acceptor Azo Dyes in Anaerobic Respiration

Abstract: Bacterial anaerobic respiration using an extracellular electron acceptor plays a predominant role in global biogeochemical cycles. However, the mechanisms of bacterial adaptation to the toxic organic pollutant as the extracellular electron acceptor during anaerobic respiration are not clear, which limits our ability to optimize the strategies for the bioremediation of a contaminated environment. Here, we report the physiological characteristics and the global gene expression of an ecologically successful bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…When the microbial cells encounter a chemical stimulus like dyes, these respond by altering physiology in multifarious ways. The previous reports on transcriptome analysis of the azo-dye respiring or degrading strains have revealed that dyes induce the expressions of genes associated with chemotaxis, signal transduction, motility, DNA and protein damage repair, and oxidative stress [ 65 ]. Based on this, a meticulous inspection of the ORFs encoding several critical proteins dedicated to these functions was conducted (Additional files 10 , 11 , 12 , 13 , 14 and 15 ), and a model for the mechanism of dye co-metabolism was hypothesized (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…When the microbial cells encounter a chemical stimulus like dyes, these respond by altering physiology in multifarious ways. The previous reports on transcriptome analysis of the azo-dye respiring or degrading strains have revealed that dyes induce the expressions of genes associated with chemotaxis, signal transduction, motility, DNA and protein damage repair, and oxidative stress [ 65 ]. Based on this, a meticulous inspection of the ORFs encoding several critical proteins dedicated to these functions was conducted (Additional files 10 , 11 , 12 , 13 , 14 and 15 ), and a model for the mechanism of dye co-metabolism was hypothesized (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…S. decolorationis S12 was isolated from the activated sludge of a textile-wastewater treatment plant (Xu et al, 2005). S12 mutants and complemented strains were constructed using the methods described previously (Fang et al, 2019). Escherichia coli and S. decolorationis strains were cultured aerobically in LB medium at 37 and 30 • C, respectively.…”
Section: Bacterial Strains Plasmids and Growth Conditionsmentioning
confidence: 99%
“…Plasmid pHGM01 was used to construct the mutant strains with Ap r , Gm r , Cm r , and att-based suicide vector. Plasmid pHG102 was used to construct the complemented strains with Km r and the S. oneidensis arcA promoter vector (Fang et al, 2019). Gentamycin (15 µg/mL), ampicillin (50 µg/mL), or 2,6-diaminopimelic acid (30 µM) were added to the medium as necessary.…”
Section: Bacterial Strains Plasmids and Growth Conditionsmentioning
confidence: 99%
See 2 more Smart Citations